Ben Yokoyama and the cookie of endless waiting - Swanson, Matthew, 1974- (Swanson, Matthew, 1974- Cookie chronicles, 2021)
A fortune cookie convinces Ben he can have whatever he wants if he is willing to wait, but getting paired with eccentric former friend Walter for a school scavenger hunt leads to unexpected rewards.